Breaking Down the Barriers to Regional Agricultural Trade in Central Africa - World Bank Group (World Bank, Washington, DC, 2018)
Despite the region’s vast potential for agriculture production and trade, the agriculture sector in Central African economic and monetary community (CEMAC) remains largely underdeveloped. This study supports CEMAC countries in their efforts to diversify their economies through increased agricultural trade. Findings focus on the costs and constraints associated with large and small-scale agriculture trade, including procedures faced at the border and in nearby assembly markets. This analysis uses a corridor approach to understand current conditions at selected border crossings and in nearby assembly markets that are important to regional agriculture trade in CEMAC, following commodities through six points on the supply chain: farm, immediate market, collection market, urban market, border market, and foreign market. The report is centered on Cameroon, as currently CEMAC’s main agricultural producer and exporter. Despite a large potential across the CEMAC region, Cameroon is at the moment by far the largest producer as well as the only significant exporter of agricultural products. The report is organized around thirteen key messages that cover production, sourcing, and trade. The final section lists recommendations and areas for potential investment and policy reform that can help the region implement its trade integration ambitions in the service of food security, agricultural development, and economic diversification.